A High-Coverage Yersinia pestis Genome from a Sixth-Century Justinianic Plague Victim. (30th August 2016) - Feldman, Michal; Harbeck, Michaela; Keller, Marcel; Spyrou, Maria A.; Rott, Andreas; Trautmann, Bernd; Scholz, Holger C.; Päffgen, Bernd; Peters, Joris; McCormick, Michael; Bos, Kirsten; Herbig, Alexander; et al.
Abstract: The Justinianic Plague, which started in the sixth century and lasted to the mid eighth century, is thought to be the first of three historically documented plague pandemics causing massive casualties. Historical accounts and molecular data suggest the bacterium Yersinia pestis as its etiological agent. Here we present a new high-coverage (17.9-fold) Y. pestis genome obtained from a sixth-century skeleton recovered from a southern German burial site close to Munich. The reconstructed genome enabled the detection of 30 unique substitutions as well as structural differences that have not been previously described. We report indels affecting a lacl family transcription regulator gene as well as nonsynonymous substitutions in the nrdE, fadJ, and pcp genes, that have been suggested as plague virulence determinants or have been shown to be upregulated in different models of plague infection. In addition, we identify 19 false positive substitutions in a previously published lower-coverage Y. pestis genome from another archaeological site of the same time period and geographical region that is otherwise genetically identical to the high-coverage genome sequence reported here, suggesting low-genetic diversity of the plague during the sixth century in rural southern Germany.